Brominated Flame Retardants: A Literature Review of The Toxicity Mechanisms, Clinical Manifestations, And Current Treatments - Prasetyo, Yacobus Christian; Sholikhah, Eti Nurwening (UI Scholars Hub, 2023)
Brominated flame retardants (BFRs) are organohalogen compounds that can inhibit fire formation and delay its spread in manufacturing materials. BFRs are known to be toxic for the environment and humans. BFRs could persist for years prolonging potential exposure and toxicity to living beings. Indonesia had begun to reduce the use, even though some of toxic BFRs are still illegally circulating. This review aims to describe some aspects of BFRs toxicity including the mechanism, its clinical manifestations, and the current possible treatments. Toxicity after BFRs exposure includes endocrine, neurodevelopmental, and genotoxicity. The toxicity is manifested into some clinical conditions such as hypothyroidism, gonadal disturbance, or neurological disorders. Currently no definitive specific treatment is available, so the treatment is focused on primary survey as well as surface decontamination with running water and gastrointestinal decontamination with activated charcoal of some dose if the ingestion is less than 1 hour.